2020
DOI: 10.1007/s40194-020-00880-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of a highly productive GMAW hot wire process using a two-dimensional arc deflection

Abstract: Gas metal arc welding (GMAW) processes are used in a wide range of applications due to their high productivity and flexibility. Nevertheless, the supplied melting wire electrode leads to a coupling of material and heat input. Therefore, an increase of the melting rate correlates with an increase of the heat input by the arc at the same time. A possibility to separate material and heat input is to use an additional wire, which reduces penetration and worsens the wetting behaviour. Consequently, bead irregularit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Based on the research conducted by the authors on the use of a magnetic arc de ection to increase productivity in GMAW hot wire welding, the potential of such a process for highly productive joint welding was demonstrated [31]. These investigations showed that 8 mm plates of 1.0045 with a Y-seam preparation and a web of 2 mm could not be welded without backing.…”
Section: Joint Welding 8 MM Sheetsmentioning
confidence: 99%
“…Based on the research conducted by the authors on the use of a magnetic arc de ection to increase productivity in GMAW hot wire welding, the potential of such a process for highly productive joint welding was demonstrated [31]. These investigations showed that 8 mm plates of 1.0045 with a Y-seam preparation and a web of 2 mm could not be welded without backing.…”
Section: Joint Welding 8 MM Sheetsmentioning
confidence: 99%
“…Because of its high specific strength, strong machinability, excellent corrosion resistance, and other performance advantages [1], 6061 aluminum alloy is widely used in modern essential equipment manufacturing sections, including aerospace [2,3], shipbuilding [4,5], transportation [6,7], etc. MIG (metal inert gas arc welding) technology is often applied in recent manufacturing methods of aluminum alloy complex structures of medium plate due to its high quality, high efficiency, and high flexibility [8]. However, molten pool depression and the thermal crack are prone to occur due to the difficulty of regulating the thermal force effect of the conventional process during the 6061 aluminum alloy welding [9].…”
Section: Introductionmentioning
confidence: 99%
“…Welding processes that involve a hybridization of the hot-wire method (e.g., gas tungsten arc welding (GTAW), GMAW, submerged arc welding, laser welding) have been investigated and applied to improve productivity in fields beyond the construction machinery industry [11][12][13][14][15][16][17][18][19][20][21][22]. The welding phenomena and optimization of hot-wire feeding conditions have been investigated for the GTAW process [23].…”
Section: Introductionmentioning
confidence: 99%